2020
DOI: 10.18203/2320-1770.ijrcog20200332
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of prenatal screening methods for detection of risk of fetal chromosomal abnormalities

Abstract: Background: Babies born with chromosomal abnormalities pose a burden on the family as well as the society at large. Early detection and management of fetal chromosomal abnormalities has become an essential component of antenatal care. Hence pregnant women of all ages are offered screening methods for early detection of chromosomal abnormalities. We intended to study the sensitivity and specificity of prenatal screening methods for detection of risk of fetal chromosomal abnormalities.Methods: A three-year retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In a three-year retrospective study conducted in Punjab, India, it was observed that the sensitivity and specificity of dual marker test for detection of chromosomal abnormality is 50% and 85.94% respectively and that of quadruple test sensitivity is 50%, specificity is 95.3% when the results were confirmed with invasive test. 26 Another study stated that the false positive rate for the biochemical screening tests is 5%, while the positive predictive value is 2-5%. 25 To determine the true false positives and the positive predictive values of the maternal screening marker tests and NIPT in our study, the high-risk patients would need to be followed up with an invasive diagnostic test such as karyotyping test, which is one of the limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In a three-year retrospective study conducted in Punjab, India, it was observed that the sensitivity and specificity of dual marker test for detection of chromosomal abnormality is 50% and 85.94% respectively and that of quadruple test sensitivity is 50%, specificity is 95.3% when the results were confirmed with invasive test. 26 Another study stated that the false positive rate for the biochemical screening tests is 5%, while the positive predictive value is 2-5%. 25 To determine the true false positives and the positive predictive values of the maternal screening marker tests and NIPT in our study, the high-risk patients would need to be followed up with an invasive diagnostic test such as karyotyping test, which is one of the limitations of this study.…”
Section: Discussionmentioning
confidence: 99%